Effect of Steam Explosion on the Release of Nutrients and Digestibility of Black Barley - Jie WANG; Zhilong ZENG; Haoyuan WANG; Manman LU; Yao LI; Chuanhu YI; Xiong LIU (Shipin gongye ke-ji)
This study investigates the effects of steam explosion (SE) on the nutrient composition and digestibility of black barley. Under different SE pressures (1.8, 2.0, 2.4 MPa), SE times (20, 30, 40 s), and initial moisture contents (8%, 10%, 12%), the contents of β-glucan, polyphenols, and flavonoids, as well as the swelling degree, pasting degree, and starch hydrolysis index of black barley were analyzed. Results showed that SE treatment increased the free polyphenol content by up to 124.37% and the RS content by up to 198.05%. With increasing pressure and time, free polyphenol content increased (with a maximum increase of 64.46%), while β-glucan and free flavonoid contents decreased, and swelling and pasting degrees increased. The internal structure of black barley became more porous, and the starch hydrolysis index showed an upward trend. Increasing the initial moisture content enhanced the levels of β-glucan, bound polyphenols, and bound flavonoids. To ensure the processing quality of black barley, while considering its nutritional, physical, and digestibility properties, it is recommended to use SE conditions of at least 2.0 MPa pressure, 10%~12% initial moisture content, and 30~40 s treatment time. Although the free polyphenol content varied significantly under different SE conditions, the starch hydrolysis index of fully gelatinized samples showed no significant differences, indicating that free polyphenols could not inhibit starch digestion in the complex system of black barley. This study provides theoretical references for the processing and utilization of black barley products.